Dreamtime : Zeitgenössische Aboriginal Art. - Akerman, Kim; Eather, Bronwyn; Eather, Michael; Essl, Karlheinz; Nicholls, Christine; Watson, Sam; West, Margie (Klosterneuburg (Wien) : Sammlung Essl Kunst der Gegenwart, 2001)
Bardayal Nadiamerrek, Lofty ; Bell, Richard ; Bennett, Gordon ; Binyinyiwuy ; Brown, Jonathan Kumintjara ; Campfire Group ; Dhamarrandji, Gunguyuma ; Djukulul, Dorothy ; Downs, Jarinyanu David ; Dorrng, Micky ; Gudapi, Willi ; Hobson, Samantha ; Jagamara, Michael Nelson ; Jaminji, Paddy Jampin ; Jampitjinpa, Kaapa Mpetyane ; Jangala, Abie (Walpajirri) ; Kantilla, Kitty ; Karedada, Lily Mindildil ; King-Smith, Leah ; Kngwarreye, Emily Kame ; Kubarkku, Mick ; Marawili, Wakuthi ; Marika, Mathaman ; Mawurndjul, John ; McKenzie, Queenie Nakarra ; Milpurrurru, George ; Mowaljarlai, David Banggal ; Mung Mung, Georg Jampin ; Namok, Rosella ; Nampitjin, Eubena (Yupinya) ; Napanangka, Makinti ; Napanangka, Pirrmangka ; Napangardi, Maggie Watson ; Napangardi Robinson, Dorothy ; Napangati, Bai Bai ; Napurrula, Mitjili ; Nickolls, Trevor ; Numbulmoore, Charlie ; Nyadbi, Lena Nyawurru ; Onus, Lin ; Petyarre, Gloria Tamerre ; Petyarre, Kathleen ; Pwerle, Angelina ; Riley Munduwalawala, Ginger ; Serico, Vincent ; Skipper, Peter (Kurrapa Pijaju) ; Thomas, Rover Julama ; Tjakamarra, Anatjari ; Tjampitjin, Sunfly ; Tjampitjinpa, Old Walter ; Tjampitjinpa, Ronnie ; Tjangala, Uta Uta ; Tjapaltjarri, Clifford Possum ; Tjapaltjarri Namarari, Mick ; Tjapaltjarri, Walala ; Tjapanangka, Long Tom ; Tjapangarti, Wimmitji ; Tjungarrayi, George ; Tjungurrayi, Yala Yala Gibbs ; Tjupurrula, Donkeyman Lee ; Tjupurrula, Johnny W. ; Tjupurrula, Turkey Tolson ; Yirawala, Billy
biog. p.246-287, biog. auteurs p. 288-290, literatuur p. 298-300
Duits & Engels
Dreamtime : Zeitgenössiche Aboriginal Art / the dark and the light, Sammlung Essl Kunst der Gegenwart, Klosterneuburg (Wien), 18.05. - 30.09.2001
boek
Keywords: Australië